1976
DOI: 10.1002/eji.1830060310
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between storage and secretion of specific antibody by immune lymphoid cells: ultrastructural localization of anti‐peroxidase anti bodies in plaque‐forming cells of the rabbit popliteal lymph node

Abstract: The ultrastructure of antibody-forming cells (AFC) has been studied in the lymph node cell population from rabbits locally immunized with horseradish peroxydase (PO) incorporated in complete Freund's adjuvant, and the kinetics of AFC development followed from day 7 to day 18 after one injection of PO. Identification of the AFC was done by local hemolysis assay, using carboxymethyl cellulose solidifying medium and PO-coated sheep erythrocytes. AFC were thereafter transferred by micromanipulation into a Beem ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…It is also unclear why many AFC exhibit such dilated RER in our cultures. It has been suggested that extensive RER dilatation may be associated with decreased antibody secretion (14), and we wonder whether dilated RER results in the strongest staining for cytoplasmic Ig in immunocytochemical assays. It is possible that the maturation into typical plasma cells functions to limit the amount of Ig secreted in an immune response.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is also unclear why many AFC exhibit such dilated RER in our cultures. It has been suggested that extensive RER dilatation may be associated with decreased antibody secretion (14), and we wonder whether dilated RER results in the strongest staining for cytoplasmic Ig in immunocytochemical assays. It is possible that the maturation into typical plasma cells functions to limit the amount of Ig secreted in an immune response.…”
Section: Discussionmentioning
confidence: 95%
“…Some cells ( Fig. 4 D) exhibited large dilated cisternae corresponding to Mott cell droplets (13,14). A sample differential of a typical 3-day culture of LPS blasts is presented in Table V.…”
Section: Differentiation Of the Cultured Lymphoblastmentioning
confidence: 99%
“…In contrast to anti-PO Ab-secreting cells from immunized animals which show heterogenous ultrastructural characteristics and are identified as either lymphocytes, proplasmocytes or plasmocytes, all the PO 772 C 2 cells showed the same ultrastructural pattern and were identified as proplasmocytes. Moreover, taking advantage of the PO penetration into fixed cells and the PO staining after enzymatic reaction [16], we studied the presence of Ab inside the cells and at the cell surface. EM observations showed Ab within the cisternae of the RER.…”
Section: Discussionmentioning
confidence: 99%
“…They were then processed for the detection of intracellular anti-PO Ab and finally for electron microscopic observation as described in detail elsewhere [16].…”
Section: Cytological Treatmentmentioning
confidence: 99%
“…After antigenic challenge, proliferation of lymphocytes from the B lineage ultimately leads to the development of specific antibody-forming cells (Nieuwenhuis, 1981). Although plasma cells are generally considered to be the main antibody-producing cells, the population of cells responsible for antibody synthesis is morphologically heterogeneous: besides plasma cells, considerable numbers of antibody-forming lymphocytes, antibodyforming plasmablasts, and antibody-forming immature plasma cells were observed (Zagury et al, 1976;Geldof et al, 1984b). It has been observed that more mature antibody-forming cells tended to localize nearer the medulla and more immature cells nearer the cortex, in both the TD immune response against TNP-KLH (Van Rees et al, 1986) and the TI immune response against TNP-LPS (Van Rees et al, 1987).…”
Section: Morphology Of Specific Antibody-forming Cells In Lymph Nodesmentioning
confidence: 99%